FeCo alloys in-situ formed in Co/Co2P/N-doped carbon as a durable catalyst for boosting bio-electrons-driven oxygen reduction in microbial fuel cells. (15th January 2022) - Xu, Xin; Xie, Jiahao; Dai, Ying; Yang, Liu; Cai, Zhuang; Jing, Baojian; Zou, Jinlong
Abstract: Non-noble metal catalyst with high catalytic activity and stability towards oxygen reduction reaction (ORR) is critical for durable bioelectricity generation in air-cathode microbial fuel cells (MFCs). Herein, nitrogen-doped (iron-cobalt alloy)/cobalt/cobalt phosphide/partly-graphitized carbon ((FeCo)/Co/Co2 P/NPGC) catalysts are prepared by using cornstalks via a facile method. Carbonization temperature exerts a great effect on catalyst structure and ORR activity. FeCo alloys are in-situ formed in the catalysts above 900 °C, which are considered as the highly-active component in catalyzing ORR. AC-MFC with FeCo/Co/Co2 P/NPGC (950 °C) cathode shows the highest power density of 997.74 ± 5 mW m −2, which only declines 8.65% after 90 d operation. The highest Coulombic efficiency (23.3%) and the lowest charge transfer resistance (22.89 Ω) are obtained by FeCo/Co/Co2 P/NPGC (950 °C) cathode, indicating that it has a high bio-electrons recycling rate. Highly porous structure (539.50 m 2  g −1 ) can provide the interconnected channels to facilitate the transport of O2 . FeCo alloys promote charge transfer and catalytic decomposition of H2 O2 to OH and O2 −, which inhibits cathodic biofilm growth to improve ORR durability. Synergies between metallic components (FeCo/Co/Co2 P) and N-doped carbon energetically improve the ORR catalytic activity of (FeCo)/Co/Co2 P/NPGC catalysts, which have the potential to be widely used as catalysts in MFCs. Graphical abstract: Image 1 Highlights: Residual cornstalks as the recycling carbon source are environmental-friendly. FeCo alloy anchored in N-doped carbon improves ORR catalytic activity in AC-MFCs. Porous carbon structure with doped N-species facilitates the O2 transport for ORR. AC-MFC with FeCo/Co/Co2 P/NPGC (950 °C) cathode has higher power output than Pt/C. FeCo/Co/Co2 P/NPGC catalyst shows a good durability for long-time AC-MFCs operation.